ANALISIS PENDAPATAN NELAYAN BERDASARKAN SISTEM BAGI HASIL PADA KAPAL PUKAT CINCIN (PURSE SEINE) DI PPN SIBOLGA SUMATERA UTARA - Yunita Friska Sitanggang; Darlim Darmawi; Farhan Ramdhani; Jecky Silaban; M Hariski; Bagus Pramusintho; Firmansyah Firmansyah (Universitas Teuku Umar, 2025)
Pelabuhan Perikanan Nusantara (PPN) Sibolga, a key capture fisheries hub in North Sumatra, supports a range of services and activities for fishing stakeholders. Purse seine vessels, predominantly used by fishermen at PPN Sibolga, target pelagic species such as kawakawa (Euthynnus affinis), yellowfin tuna (Thunnus albacares), and skipjack tuna (Katsuwonus pelamis). This study analyzes income disparities among fishermen based on the profit-sharing system applied to purse seine vessels at PPN Sibolga. Conducted from March 4 to April 4, 2024, the study employed a survey method, collecting primary data on fish weight (kg), selling price (IDR), vessel size (GT), and operational costs, alongside secondary data on fishing gear statistics and regional information from PPN Sibolga. Data were analyzed descriptively to elucidate the income-sharing structure. Findings indicate that the average operational cost per trip for a purse seine vessel is IDR 199,458,550, with an average revenue of IDR 443,046,000 and a net profit of IDR 232,597,867. The profit-sharing system allocates 60% of the net profit (after fixed costs) to the vessel owner and 40% to the crew, with the skipper receiving 8.10%, senior crew (engineers, officers, cooks) 5.40%, supporting crew 4.05%, and regular crew 2.70%. The study reveals significant income disparities among crew members, driven by their roles and the established profit-sharing structure in purse seine operations at PPN Sibolga